Islamic Legal Problematics in Legal Politics: Examination of the Roots of Islamic Law Controversy in Indonesia - Maslawani (PT Maju Malaqbi Makkarana, 2024)
The research results show that the roots of Islamic law controversy in legal politics in Indonesia stem from several problems such as; differences in perceiving Islam, differences in legal basis/sources, theoretical understanding of Islamic law, controversy between religious figures and nationalists, controversy between Muslims and non-Muslims. Controversy seems to continue to accompany the government's efforts to implement Islamic law (Shariah) as a policy framework, especially in regulations or laws. The ratification of a regulation into a form of law is closely related to the legal political policies maintained by society and the government in a country. Thus, the idea emerged that law emerged from the political process or, conversely, politics emerged from the legal process. These two different views greatly influence the highest decision-making power in a state or country. Based on the research results, it shows that the problems of Islamic law in Indonesia consist of three areas: First, they are distributed in the Fiqh books written by the Fuqaha; Second, it is included in State regulations containing Islamic law; Third, it is included in the judge's decision in the form of jurisprudence. The application of these three sources of Islamic law often creates controversy between fiqh and existing regulations, between fiqh and court decisions, and between court decisions and existing regulations